Compliance with the EAT-Lancet diet and risk of colorectal cancer: a prospective cohort study in 98,415 American adults - Ren, Xiaorui; Yu, Chuanchuan; Peng, Linglong; Gu, Haitao; Xiao, Yi; Tang, Yunhao; He, Hongmei; Xiang, Ling; Wang, Yaxu; Jiang, Yahui (Frontiers in Nutrition, 2023)
Background The EAT-Lancet diet (ELD) is a recommended dietary pattern for achieving simultaneous improvements in both individual health and environmental sustainability. While research on the association between ELD and colorectal cancer (CRC) remains scarce, the potential impact of nutrition on CRC prevention and progression is a topic of growing interest. This study aims to investigate the relationship between adherence to the ELD and the risk of CRC, shedding light on the role of nutrition in CRC prevention. Methods A total of 98,415 participants were included. A Diet History Questionnaire (DHQ) was used to collect dietary information, and an ELD score was used to assess adherence to ELD. Higher scores indicated greater adherence. Cox hazard regression analyses were conducted to examine whether there were associations between the ELD score and CRC risk. The restricted cubic spline (RCS) model was used to further explore the dose-response association between the ELD score and CRC incidence. Subgroup analyses were conducted to identify potential modifiers that interacted with ELD on CRC incidence, and sensitivity analyses were performed to evaluate the robustness of the established association. Results During a mean follow-up of 8.82 years, a total of 1,054 CRC cases were documented. We found a statistically significant correlation between the ELD score and CRC risk (Q4 vs. Q1: HR 0.81, 95% CI 0.67–0.98; P for trend = 0.034) after adjusting for potential confounders. No statistically significant associations were discovered between ELD adherence and CRC by anatomical site. Subgroup analyses found no interactional factor, sensitivity analyses, and the RCS model showed a robustness and linearity association (P-linearity >0.05). Conclusion We concluded that adherence to ELD contributes to the prevention of CRC.